A FRET-based study reveals site-specific regulation of spindle position checkpoint proteins at yeast centrosomes - Gryaznova, Yuliya; Caydasi, Ayse Koca; Malengo, Gabriele; Sourjik, Victor; Pereira, Gislene (eLife, 2016)
Daughter-cell-associated factors and centrosome-based regulation is important in mitotic exit and spindle position checkpoint control.